Cinemelography, Visible Language of Music - Borjan, Etami (2009)
Although Luigi Pirandello is a world-renowned writer his works on cinema are not widespread. The paper compares his ideas with the existent theories on cinema in Italy in the first decades of the 20th century. His article “ Can sound cinema destroy theatre” was written in 1929, one year before the release of the first sound film in Italy. In the period of the first reproductions of sound in cinema there were lively discussions among artists and intellectuals about possible fusion between cinema and theatre. In his article Pirandello praised the cinematic expression, until then considered an artisan practice, demonstrating that cinema was a form of art based on its proper means of expression: image and sound. According to the author, cinema should detach itself from literature and theatre in order to develop an autonomous artistic expression. Pirandello gave a name to the new cinema that should emerge from the fusion of image and music: cinemelography, visible language of music. Although Pirandello wasn’ t a film critic and there aren’ t many elaborated works on film theory in his literary opus, his essays as well as the first novel about filmmaking (Shoot! The Notebooks of Serafino Gubbio, Cinematograph Operator 1915), were serious attempts to define the nature of the new media and to find new linguistic expressions that should separate it from other forms of art.